PELAKSANAAN PENILAIAN AKHIR MAGANG KEPENDIDIKAN 3 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET SURAKARTA (Studi Kasus di SMK N 6 Surakarta Tahun Ajaran 2019/2020) - Firli Khoirul Rachmadani; Anton Subarno; Wiedy Murtini (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
Abstract The Implementation Of Teaching Internship 3 Of  Teacher Taining and Education Facultyebelas Maret University (Case Study Of Final Assessment Internship Program At Vocational Senior High School 6 Surakarta 2018/2019). This research aims to find ; 1) the implementation of teaching Internship 3, 2) the Problems in the teaching internship, and 3) the way of solving  the problems of teaching internship 3 at Vocational Senior High School 6 Surakarta. This research is a qualitative research ith a case study approach. The sampling technique was purposive and snowball sampling methods, the head of the teaching internship 3 is as the key-informant. The data were collected using interview, observation, and documentation. The  validation of data was the source triangulation and method triangulation. The data were analysed using reduction, data display, and conclusion drawing/verification. The results show: 1) the implementation of the final assessment of teaching internship program was not in accodance with its  guidlines, 2) the problems of teaching internship, for instance lack of coordination between students, lecturer, UP2KTM, and high school teachers during the teaching internship program, the purpose of teaching internship was not in step with the internship guilines, the quality of instruments of the teaching internship, an inadequate assessment form, and a limited number of student who have abilities in the extracuricular field, and 3) the effort to overcoming the problems, such as increasing coordination between students, lecturers, UP2KTM, and high schools teachers, the evaluation of internship goal based on UP2KTM, evaluation of teaching intership guidlines instruments by UP2KTM, and the evaluation of assement system on extracurricular activities.